Hybrid maize seed supply in Ghana - Tripp, Robert; Ragasa, Catherine (International Food Policy Research Institute, 2015)
This paper examines factors related to the supply of hybrid maize seed in Ghana and lays the groundwork for research on the demand side. There are a number of public maize hybrids, but most are recently released and only a few are readily available to farmers. There has also been importation of hybrid maize seed, but this is now severely restricted. The current system for variety release is undergoing modification and has proven particularly unsatisfactory for imported hybrids. One of the major challenges in promoting the public hybrids has been an inef-ficient source seed system, and this has affected the prospects of the relatively few emerging domestic seed companies that are attempting to produce and market local hybrids. There are also serious deficiencies in mar-keting local hybrids. Problems in local hybrid production and marketing and small quantities of imported seed mean that only a small minority of farmers have experience with maize hybrids. The paper also looks at the regu-latory and policy issues affecting hybrid maize promotion and examines the interplay between the substantial portfolio of donor projects supporting the seed sector and government stances and priorities. The paper con-cludes with a consideration of priorities for seed system development and a preliminary assessment of the imme-diate prospects for hybrid maize seed supply in Ghana.